Dendritic Spikes Are Enhanced by Cooperative Network Activity in the Intact Hippocampus - Kamondi, Anita (J Neurosci, 1998)
In vitro experiments suggest that dendritic fast action potentials may influence the efficacy of concurrently active synapses by enhancing Ca(2+) influx into the dendrites. However, the exact circumstances leading to these effects in the intact brain are not known. We have addressed these issues by performing intracellular sharp electrode recordings from morphologically identified sites in the apical dendrites of CA1 pyramidal neurons in vivo while simultaneously monitoring extracellular population activity. The amplitude of spontaneous fast action potentials in dendrites decreased as a function of distance from the soma, suggesting that dendritic propagation of fast action potentials is strongly attenuated in vivo. Whereas the amplitude variability of somatic action potentials was very small, the amplitude of fast spikes varied substantially in distal dendrites. Large-amplitude fast spikes in dendrites occurred during population discharges of CA3–CA1 neurons concurrent with field sharp waves. The large-amplitude fast spikes were associated with bursts of smaller-amplitude action potentials and putative Ca(2+) spikes. Both current pulse-evoked and spontaneously occurring Ca(2+) spikes were always preceded by large-amplitude fast spikes. More spikes were observed in the dendrites during sharp waves than in the soma, suggesting that local dendritic spikes may be generated during this behaviorally relevant population pattern. Because not all dendritic spikes produce somatic action potentials, they may be functionally distinct from action potentials that signal via the axon.